2022
DOI: 10.3390/electronics11152307
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Power Output from a Crystalline Silicon Photovoltaic Module with Repaired Cell-in-Hotspots

Abstract: Recycling of problematic photovoltaic modules as raw materials requires considerable energy. The technology to restore cells in hotspot modules at a relatively low cost is more economical than replacing them with new modules. Moreover, a technology that restores power by replacing a cell-in-hotspot of a photovoltaic module with a new cell rather than replacing the whole module is useful for operating power plants. In particular, power plants that receive government subsidies have to use certified modules of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…According to the previous study, in the restoration of the back surface field (BSF) type cell, which is an early model of the crystalline silicon solar cell, almost no decrease in output due to cell deterioration was observed. [30] The cell taken for this experiment was of passivated emitter rear contact (PERC) type, which was the next generation of BSF cells, and in this case, it was found that the higher the initial efficiency, the higher the degradation rate of the cell when the module is restored. The decrease in output was mainly caused by a decrease in V mp , which can be found in the increase of series resistance elements due to cell deterioration.…”
Section: Resultsmentioning
confidence: 96%
“…According to the previous study, in the restoration of the back surface field (BSF) type cell, which is an early model of the crystalline silicon solar cell, almost no decrease in output due to cell deterioration was observed. [30] The cell taken for this experiment was of passivated emitter rear contact (PERC) type, which was the next generation of BSF cells, and in this case, it was found that the higher the initial efficiency, the higher the degradation rate of the cell when the module is restored. The decrease in output was mainly caused by a decrease in V mp , which can be found in the increase of series resistance elements due to cell deterioration.…”
Section: Resultsmentioning
confidence: 96%
“…The loss due to the electrical mismatch of the cell has been published as a concept called RPL (relative power loss), which is not precisely defined and classified before the CTM factor [48]. RPL is expressed as the difference between the maximum power (Pmpc) of n individual cells connected in series to form a cell string or module and the output power of the cell string.…”
Section: Theoretical Background To Module Output Analysismentioning
confidence: 99%
“…In a previous study [48] that reported repairs of a waste module containing some damaged cells by replacing it with a new cell, it which was checked whether the same results were obtained even when the module type was different as a single crystal. The cell replacement experiment followed the sequence from previous studies.…”
Section: Basic Experiments According To Previous Research Proceduresmentioning
confidence: 99%
“…They could lead to electrically disconnected cell regions, causing a decrease in short-circuit current and shunt resistance 24 , subsequently reducing the module's power output 25 . Cracks may also develop in the PV module if there are localised hotspots 26,27 .…”
Section: Introductionmentioning
confidence: 99%